Lectin complement pathway initiators after subarachnoid hemorrhage — an observational study - Jeppe Sillesen Matzen (Journal of Neuroinflammation, 2020)
Abstract Background This exploratory study investigated the time-course of lectin complement pathway (LCP) initiators in cerebrospinal fluid (CSF) and plasma in patients with subarachnoid hemorrhage (SAH), as well as their relationship to delayed cerebral ischemia (DCI) and functional outcome. Methods Concentrations of ficolin-1, ficolin-2, ficolin-3, and mannose-binding lectin (MBL) were analyzed in CSF and plasma from patients with SAH. Samples were collected daily from admission until day 9 (CSF; N_PATIENTS = 63, n_SAMPLES = 399) and day 8 (plasma; N_PATIENTS = 50, n_SAMPLES = 358), respectively. Twelve neurologically healthy patients undergoing spinal anesthesia and 12 healthy blood donors served as controls. The development of DCI during hospitalization and functional outcome at 3 months (modified Rankin Scale) were registered for patients. Results On admission, CSF levels of all LCP initiators were increased in SAH patients compared with healthy controls. Levels declined gradually over days in patients; however, a biphasic course was observed for ficolin-1. Increased CSF levels of all LCP initiators were associated with a poor functional outcome in univariate analyses. This relationship persisted for ficolin-1 and MBL in multivariate analysis after adjustments for confounders (age, sex, clinical severity, distribution and amount of blood on CT-imaging) and multiple testing (1.87 ng/mL higher in average, 95% CI, 1.17 to 2.99 and 1.69 ng/mL higher in average, 95% CI, 1.09 to 2.63, respectively). In patients who developed DCI compared with those without DCI, CSF levels of ficolin-1 and MBL tended to increase slightly more over time (p_interaction = 0.021 and 0.033, respectively); however, no association was found after adjustments for confounders and multiple testing (p-adj_interaction = 0.086 and 0.098, respectively). Plasma ficolin-1 and ficolin-3 were lower in SAH patients compared with healthy controls on all days. DCI and functional outcome were not associated with LCP initiator levels in plasma. Conclusion Patients with SAH displayed elevated CSF levels of ficolin-1, ficolin-2, ficolin-3, and MBL. Increased CSF levels of ficolin-1 and MBL were associated with a poor functional outcome. Trial registration This study was a retrospective analysis of samples, which had been prospectively sampled and stored in a biobank. Registered at clinicaltrials.gov ( NCT01791257 , February 13, 2013, and NCT02320539 , December 19, 2014).